4 PENGARUH HARGA DIRI, REGULASI DIRI, DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI AKADEMIK SISWA AKSELERASI - Zuhdi, Muhammad Sholihuddin (Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT One's academic achievement is influenced by many aspects, one of the aspects that affect academic achievement is the psychological aspects including self-esteem, self-regulation, and achievement motivation. A person who has self-esteem, self-regulation, and high achievement motivation was possible to have high academic achievement. This study aimed to test theoretical models to test students' academic performance acceleration and influence between variables using data analysis is a statistical test of the structural equation modeling (SEM) The results of hypothesis testing through SEM analysis, we concluded that the theoretical models of student achievement accelerated program has proven its worth (GFI = 0924 criteria> 0.900) and obtain the support of empirical data (X2 = 149 799, p = 0398 criteria> 0.05), as well as self-esteem affect achievement motivation, self regulation affecting achievement motivation, self-esteem affect academic achievement, self-regulation affects academic achievement, and achievement motivation affect academic achievement. Key words: Self-esteem, self-regulation, achievement motivation and academic achievement